Can high price earnings ratio act as an indicator of the coming bear market in the Malaysia? - Ong, Tze San; Yichen, Yantoultra Ngui; Teh, Boon Heng (Center for Promoting Ideas, 2010)
This paper explores the capability of value investing strategy on the prediction of stock performance, but with regards to the fall in stock prices in Malaysia. The methodology employed is based mostly on fundamental analysis and financial markets theory. This is in line with the methods commonly used by investment analysts in all brokerage houses to evaluate shares. Based on the literature review done, the PE ratio could have been employed to build successful investment strategies in predicting stock market highs. This study explores whether this approach could be regressed and work as an indicator for forecasting of future stock market lows. To testify the hypothesis, a regression and correlation analysis is used. This study observes the development of the Malaysian stock market index, the Kuala Lumpur Composite Index (KLCI) and its PE ratio between 1994 and 2010, a time period that involves notable financial crisis such as the 1997/98 Asian financial crisis and the global financial crisis of late. Although the notions that high levels of PE Ratio could have resulted in the fall of stock market returns in the Malaysia context is rejected in this study, the results show that PE ratio is still a useful predictor of the performance of KLCI. Lastly, this research suggests the other way around, which is high level of PE ratio may precede a rise in future stock performance in the KLCI.